Improving Zakat Literacy of Managers at Nurul Huda Pajagalan Islamic Boarding School through Mentoring and Empowerment Activities - Fahmi Fatwa Rosyadi Satria Hamdani; Intan Manggala Wijayanti; Shindu Irwansyah; Nanik Eprianti; Maman Surahman (al-Afkar, Journal For Islamic Studies, 2025)
In a legal country like Indonesia, people are not allowed to establish a kind of zakat management unit without permission from the authorities (government), as explained in Law No. 23 of 2011 concerning zakat management in article 38, where everyone is not allowed to intentionally act as amil zakat without legality or permission from the authorized official. Based on the preliminary study, the manager of the Nurul Huda Pajagalan Cililin Islamic Boarding School needs skills in bookkeeping and report-making from the collection, management, and distribution of zakat. The partners then conveyed this to the service team to be able to assist in this regard. The service team conducted mentoring and empowerment activities for the managers, both from the aspect of literacy, bookkeeping of zakat objects, starting from collection, management, and distribution, as well as making zakat management reports by sharia and laws and regulations regarding zakat. The method used is participatory action research (PAR). The results of this activity show an increase in the literacy of the managers through the pre-test obtained an average value of 72.56 and the post-test obtained an average value of 128.20, so when the percentage is increased by 76.68%.